Secondary prevention after acute coronary syndrome - can we achieve dyslipidemia guideline targets?. (11th May 2021) - Martins De Carvalho, M; Proenca, T; Pinto, RA; Torres, S; Resende, CX; Grilo, P; Amador, AF; Costa, CM; Calvao, J; Marques, C; Cabrita, A; Rodrigues, JD; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Lipid control is one of the most important secondary cardiovascular prevention targets. The 4S trialin 1994 was the first study to demonstrate the benefit of statin therapy in coronary artery disease patients. More recently, the FOURIER trial (2017) and the ODYSSEY Outcomes (2018) demonstrated the cardiovascular benefit of adding a PCSK9 inhibitor to optimized antidyslipidemic therapy. Owing to the growing number of evidence showing the importance of aggressive lipid control, the European Society of Cardiology (ESC) 2019 Dyslipidemia Guidelines changed the recommendation of LDL targets from below 70 mg/dL to below 55 mg/dL in very high risk patients. In the light of this new recommendation, we retrospectively analysed all patients who participated in a Coronary Rehabilitation Program (CRP) after an Acute Coronary Syndrome at a tertiary center from May 2008 to June 2019. The CRP consisted in a multi-disciplinary approach to these patients, including 8 to 12 weekly sessions of phase II rehabilitation, exercise prescription, nutrition counselling and life-style intervention, with Cardiology follow-up at the end of the CRP (3 months), 6 months and 12 months after the event. Lipid profile was requested at baseline, 3 months and 12 months after the event. Dyslipidemia was defined using the ESC Guidelines definition. In total, 989 patients were enrolled: the mean age was 54 ± 10 years and 15% were female. Concerning to cardiovascular risk factors, 56.7% of patients had dyslipidaemia, 41.5% had hypertension, 18.1% were diabetic, 73.1% were smokers or previous smokers, 26.0% had family history of coronary disease and 14.0% had previous coronary disease. At hospital admission, mean LDL concentration was 121, 7 ± 38, 8 mg/dL with 2, 9% of the patients with values below 55 mg/dL and 7, 6% below 70 mg/dL. The vast majority of patients were medicated with statin at hospital discharge and maintained the prescription during the follow-up (97.5% and 97.1%, respectively). At the end of the CRP, there was a significant decrease of LDL values (p < 0.001) with 18.7% patients with LDL below 55 mg/dL and 46.3% below 70 mg/dL (mean LDL 76.6 ±23.6 mg/dL). At 1-year follow-up, the lipid control was better than at admission, but inferior than at the end of the rehabilitation program, both findings statistically significant (11.0% patients were below 55 mg/dL and 33.1% were below 70 mg/dL, with a mean LDL of 82.7 ± 28.3 mg/dL; p < 0.001). In conclusion, our real-life observational cohort showed that guideline recommended LDL target is not achieved in most of very high-risk patients even in a structured coronary rehabilitation program. Of note, the number of patients at LDL-target decreased from 3 months to 1-year follow-up. This state the importance of a sustained healthy lifestyle and therapy adherence, with aggressive pharmacologic therapy.